MEDIA KOMUNIKASI DIGITAL RUMAH SAKIT : ANALISIS SISTEMATIS TERHADAP EFEKTIVITAS, POTENSI DAN TANTANGAN DALAM PELAYANAN KESEHATAN PADA SKALA GLOBAL - Widiar, Restu Prihandini (LPPM Universitas Awal Bros, 2025)
Effective communication in hospitals is crucial for improving healthcare service quality. This study aims to identify effective digital health communication media used in hospitals and explore the challenges and potential of digital platforms in enhancing interactions between patients and medical professionals. The research method employed is a systematic literature review (SLR), analyzing various global research articles on hospital health communication media from 2021 to 2025. he article selection method used PRISMA (Preferred Reporting Items for Systemic Reviews and Meta-Analyses) and was reviewed with the principles of the PICO (Participants, Interventions, Comparisons and Outcomes) framework. The findings indicate that social media, mobile applications, hospital websites, telemedicine, and interactive digital media effectively enhance patient engagement, provide fast and accurate information, and facilitate medical decision-making. Additionally, digital media simplifies communication between patients and healthcare providers, particularly for those in remote locations This study concludes that integrating various digital communication media in hospitals can create a more efficient and effective communication system by optimizing the use of social media, mobile applications, and telemedicine. The research highlights the importance of developing communication models that combine multiple media types to enhance patient accessibility and engagement in their care. Future studies should include long-term analyses of the impact of communication media on patient health outcomes, as well as the need for more holistic communication models.